STRATEGIC BASIS OF THE REMOTE EVALUATION OF PATIENTS IN MOBILE MEDICINE. INFORMATION, ACCURACY, RELIABILITY - Shevchenko, Ya. O. (Medical Informatics and Engineering, 2020)
Background. The principles of remote assessment of patients in mobile medicine are analyzed. Particular attention is paid to the importance of informativeness and accuracy of indicators measured at a distance. Materials and methods. Results. The methodology of determining the integrated validity of the obtained quantitative estimates of remote monitoring is substantiated. Conclusions are made about the need to use risk indicators of predicted conditions as a universal method for determining the informativeness of symptoms in mobile monitoring of patients. Conclusion. A new approach to improving the accuracy and reliability of indicators in remote monitoring of the patient's condition, associated with the use of dynamic estimates of changes.